2020
DOI: 10.3390/ijms21083026
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-Inflammatory and Antioxidant Effects of Sodium Propionate

Abstract: The major end-products of dietary fiber fermentation by gut microbiota are the short-chain fatty acids (SCFAs) acetate, propionate, and butyrate, which have been shown to modulate host metabolism via effects on metabolic pathways at different tissue sites. Several studies showed the inhibitory effects of sodium propionate (SP) on nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) pathway. We carried out an in vitro model of inflammation on the J774-A1 cell line, by stimulation with lipopoly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 31 publications
2
29
0
Order By: Relevance
“…The gradual loss of total antioxidant protection resulted from the disrupted fermentative activity with the regular consumption of stevioside. Thus, decreased production was correlated with decreased total antioxidant status, demonstrated in previous studies [ 41 ]. The accumulation of toxic molecules due to the dysbiotic status determined a decreasing antioxidant reaction characteristic of the presence of nitrite.…”
Section: Resultssupporting
confidence: 66%
“…The gradual loss of total antioxidant protection resulted from the disrupted fermentative activity with the regular consumption of stevioside. Thus, decreased production was correlated with decreased total antioxidant status, demonstrated in previous studies [ 41 ]. The accumulation of toxic molecules due to the dysbiotic status determined a decreasing antioxidant reaction characteristic of the presence of nitrite.…”
Section: Resultssupporting
confidence: 66%
“…It suppresses the growth of mold and bacteria and maintains the quality of food. Sodium propionate suppresses LPS-induced upregulation of COX-2 and inducible NOS via the NF-κB pathway [62]. Furthermore, sodium propionate enhances anti-oxidant enzyme production such as MnSOD and HO-1 following H 2 O 2 stimulation.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, sodium propionate enhances anti-oxidant enzyme production such as MnSOD and HO-1 following H 2 O 2 stimulation. In animal models, sodium propionate reduced superoxide anion-induced inflammation, tissue damage, and pain [62]. Sodium propionate may be an effective strategy for the treatment of inflammatory diseases due to its anti-inflammatory and antioxidant effects [62].…”
Section: Methodsmentioning
confidence: 99%
“… 6 Meanwhile, propionate has been described to possess potent anti-inflammatory and anti-oxidative stress effects. 7 It has been reported that propionate normalized the increased serum levels of lipopolysaccharide (LPS) induced by high-fat diet and alleviated its induced endotoxaemia. 8 In addition, propionate protected against LPS-induced mastitis in mice.…”
Section: Introductionmentioning
confidence: 99%